IMPLEMENTASI SIKAP NASIONALISME MASYARAKAT TERHADAP PRODUK LUAR NEGERI DESA DWITUNGGAL KECAMATAN RANGSANG KABUPATEN KEPULAUAN MERANTI ( STUDI KASUS WILAYAH PERBATASAN INDONESIA-MALAYSIA) - Ahsanul Muna; Ahmad Eddison; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was made with the backgruond of nationalismin border communities releted to the dependence of border communitieson meeting the needsof life with the state of Malaysia. Dependence in the form of product circulation is dominated by products from Malaysia. So based on this phenomenon the aothorstook a study entitled “The Implementationof the Nationalism Attitudes of CommunitiesAgainst Foreign Ptoducts in Dwitunggal Village, Rangsang district, Meranti Islands Regency”. This research aims to find out how the Implementation of the NationalismAttitudes towards Foreign Products in Dwitunggal Village, Rangsang district, Meranti Islands Regency. This research is a discriptive qualitative research, whit the informants of the research are the village, using interviews. The results of the study illustrate that the implementation of the nationalism attitude of border communities abuot nationalism, love of the motherland, safeguarding what is owned by the state, willing to defendand defend and cauntry, in terms of using products originating from Malaysia to meet the necessities of life, onlu forced or no other choice. Furthermore, the reasons for the acceptance of originating from Malaysia are: lack for buyer interest in domestic products, lack of quality of domestic products rathen than foreign products, lack of goverment attention on domestic products, And coercion from the community to meet their needs. The sugestion from this research is that the government should pay more attention to border communities towars their basic needs, where teh government should concentrate more products that come from whithin the country, so people are no longer dependeent on products originating from Malaysia.Key Words: Nationalism Attitudes, Society, Foreign Products